(untitled) (Physical Education, Health and Social Sciences, 2026)
The ubiquity of public Wi-Fi in locations such as cafes, airports, and hotels offers significant convenience but simultaneously exposes users to substantial cybersecurity threats. This paper provides a systematic analysis of the security risks inherent in public wireless networks and evaluates the effectiveness of current countermeasures. Employing a methodological approach based on a comprehensive review of contemporary academic research and established cybersecurity frameworks, the study examines a range of vulnerabilities. These include classic threats like packet sniffing, evil twin access points, and man-in-the-middle attacks, as well as more sophisticated techniques such as packet-size side-channel attacks. The analysis of recent empirical studies reveals the severity of these risks, with successful TCP hijacking attacks demonstrated in 93.75% of tested real-world networks, underscoring the urgent need for robust protection. Based on this review, the paper critically assesses the efficacy of key mitigation strategies, including Virtual Private Networks (VPNs), HTTPS adoption, and secure device configurations. The findings culminate in a set of actionable recommendations aimed at enhancing the security posture of public Wi-Fi for both individual users and network providers.